2008
DOI: 10.1111/j.1532-5415.2008.01975.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Neglect and Self‐Neglect Research

Abstract: Neglect is proportionally the largest category for adult protective services referrals, yet there is a dearth of science that generates appropriate guidelines for the detection and intervention of neglect cases. Despite implementation of mandatory reporting laws and models for appropriate responding to elder neglect, there remain challenges to research in this field. These challenges include diagnosis, recruitment, retention, attrition, research language, obtaining informed consent, and many other obstacles th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Previous epidemiological studies have relied on Adult Protective Service data or over 65 years dataset such as the New Haven Established Populations for Epidemiologic Studies of the Elderly cohort . Significant barriers to research in this area have been reported as diagnoses and recruitment, language and obtaining informed consent …”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiological studies have relied on Adult Protective Service data or over 65 years dataset such as the New Haven Established Populations for Epidemiologic Studies of the Elderly cohort . Significant barriers to research in this area have been reported as diagnoses and recruitment, language and obtaining informed consent …”
Section: Discussionmentioning
confidence: 99%
“…“Self‐neglect syndrome arises from a predictive state of vulnerability in frail older adults…associated with a decline in decision‐making capacity regarding the ability to care for and protect oneself” (Naik et al, , p. 79). However, much early research excluded cognitively impaired people, limiting knowledge (Fulmer, ). Researchers then began assessing global cognitive functioning with the Mini‐Mental State Examination (MMSE; Folstein, Folstein, & McHugh, ).…”
Section: Cognitive Impairment and Elder Self‐neglectmentioning
confidence: 99%
“…This raises ethical concerns about conducting research on a vulnerable population. 13,15,16 Given the challenges of conducting research in this topic area, there is little evidence to provide guidance on whether screening for abuse is effective and which interventions to manage the risk of abuse are effective. A previous systematic review of interventions for elder abuse showed the paucity of evidence.…”
mentioning
confidence: 99%